Acesso e utilização a bases de dados: estudo de caso da Biblioteca do IFSul – Câmpus Charqueadas - Scheid, Fernando (Universidade do Vale do Rio dos Sinos, 2017)
This work aims to carry out a study about the knowledge and usage of data bases in researches done by the Graduation and Post-Graduation students of the Federal Institute Sul-rio-grandense, Campus Charqueadas, having the Library as the main scenario to understand the research profile of those users. The methodology used was a case study and the instruments of data collection were two questionnaires: the first questionnaire with closed questions including comments and suggestions and another questionnaire, used later, with open questions. After analyzing the data collection, it was concluded that many users are unaware or do not use databases (51%) to carry out their researches, but the most well-known databases are Scielo, Periódicos Capes and Web of Science. The postgraduate course uses these resources more in relation to undergraduate courses, although 19% state that they do not know or do not use databases. Among the search engines on the internet, Google had the biggest highlight, with 65%. As a suggestion of the users, the execution of training courses about these sources of information can be used more frequently. Finally, this research presents two products: the diagnosis regarding the knowledge and use of databases in research by the students of IFSul Campus Charqueadas and the proposal of a project of tutorial on the use of databases in researches to be available in Library website in order to qualify the search for information from online sources, offering another possibility of access to collections.
Keywords: Perfil de usuários; Estudo de usuários; Bases de dados; Biblioteca; User profile; Study of users; Data base; Library; ACCNPQ::Ciências Humanas::Educação